Co-ensiling of cattle manure before biogas production: Effects of fermentation stimulants and inhibitors on biomass and methane preservation. (June 2018) - Franco, Rúben Teixeira; Buffière, Pierre; Bayard, Rémy
Abstract: The impact of formic acid and glucose addition on the co-ensiling of cattle manure with straw was assessed during 4 months at laboratory scale. Feedstock deprived of additives lost 67% of its methane potential for prolonged ensiling. This was mainly due to the lack of water-soluble carbohydrates and to the high methanogenic activity of cattle manure. The use of co-substrates enhanced biomass and energy conservation during ensiling. The best result was obtained for co-ensiling of cattle manure with glucose (100 g/kg of feedstock). For this condition, lactate production was extensive, which enabled biomass acidification, suppressed ammonia emissions and led to full preservation of methane potential after 4 months. Therefore, in field-scale storage, co-ensiling with a sugar-rich co-substrate appears to be the most resourceful method to optimize cattle manure preservation. Application of this promising technique will have a major impact on the methane yield of agricultural biogas plants where cattle manure has to be stored for long periods. Highlights: Ensiling of cattle manure with straw led to 67% methane potential losses. Ammonia emissions during ensiling were minimized with the use of co-substrates. Formic acid addition limited energy losses to 25% during ensiling. Full preservation of methane potential occurred for co-ensiling with 10% of glucose.